Exploring The Effects Of Fomo (Fear Of Missing Out) And Influencer Recommendations In Driving Implusive Buying Behavior In Social Commerce - Utama, Satria Putra; Hermawan, Agus; Rahayu, Wening Patmi; Sari, Risca Kurnia (PT. Sharia Journal and Education Center, 2026)
The rapid integration of social media and e-commerce, known as social commerce, has revolutionized consumer behavior by creating a highly interactive and persuasive shopping environment. This study aims to explore the psychological and social drivers of impulsive buying behavior, specifically focusing on the effects of Fear of Missing Out (FOMO) and Influencer Recommendations. In the digital age, consumers are constantly exposed to real-time updates and curated lifestyles, which often triggers a sense of social anxiety regarding missed opportunities. Utilizing a quantitative research design, this study examines how these factors interact to bypass rational decision-making processes. Data were collected from 450 active social media users who frequently engage in social commerce platforms such as TikTok Shop and Instagram Shopping. The findings reveal that FOMO significantly intensifies the urge to purchase through the mechanism of perceived scarcity and social competition. Furthermore, influencer recommendations act as a powerful catalyst, providing social proof and lowering the perceived risk of a transaction. The synergy between FOMO and influencer credibility creates a high-pressure environment that accelerates impulsive buying. This research provides valuable insights for digital marketers in designing persuasive strategies while also offering a critical perspective for consumers to understand the psychological triggers behind their online spending habits.